Pelaksanaan Tradisi Manak Salah di Desa Padang Bulia dalam Upaya Mengakomodasi Penjaminan Hak Asasi Manusia - Kadek Dhyan Wahyuni; I Wayan Landrawan; Ni Ketut Sari Adnyani (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2026)
This study examines the implementation of the Manak Salah tradition in Padang Bulia Customary Village from the perspectives of legal certainty and human rights protection. Manak Salah is a customary practice associated with the birth of opposite-sex twins, which in Balinese Hindu cosmology is considered a sacred event that may disrupt the balance between the sekala and niskala realms, thereby requiring purification rituals. Although the contemporary practice of this tradition has become more humane and no longer involves social exclusion, its regulation remains unwritten and has not been formally codified in the village’s Awig-awig (customary law). This condition creates the risk of multiple interpretations, legal uncertainty, and insufficient protection of the rights of children and affected families. This research employs an empirical juridical method with a qualitative approach, using interviews with customary leaders, field observations, and document analysis of statutory regulations and customary legal sources. The findings reveal that the absence of written norms causes the implementation of Manak Salah to rely heavily on the discretion of customary authorities, leading to potential inconsistency and normative vulnerability. This study emphasizes the urgency of codifying the Manak Salah tradition into the Awig-awig as a form of customary law reform aimed at ensuring legal certainty, strengthening institutional accountability within customary villages, and harmonizing customary law with Bali Provincial Regulation No. 4 of 2019 and fundamental human rights principles.